Respostas morfofisiológicas de fêmeas de codornas japonesas (Coturnix coturnix japonica) criadas em diferentes fontes luminosas - Bobadilla Mendez, Manuel Fernando (2015)
The objective was to evaluate the effects of different light sources on reproductive, morphological and physiological characteristics, organ development, bone quality and body composition and liver function in females of Japanese quail (Coturnix coturnix japonica). A total of 270 birds were housed in six light-isolated rooms for 12 weeks. Each room was equipped with a different type of lamp and contained seven cages with five birds each. The tested source lights were incandescent 25-watt (400-1100 nm); compact white fluorescent (380-770 nm) and light-emitting diode (LED) in white (400-760 nm), blue (435-500 nm), red (630-700 nm) and green (500-565 nm). The luminous intensity was 15 lux and a photoperiod of 23L:1D during the first week, 7L:17E during the second to the fifth and 10L:14D until the end of the experiment. The experimental design was completely randomized with six treatments and seven repetitions of a bird each. The anatomical and physiological conditions of the reproductive tract were evaluated at 4, 8 and 12 weeks of age and morphological and physiological conditions of other systems during earlier (8 weeks) and during the peak of production (12 weeks). The white LED anticipated the sexual maturity in a week and resulted in higher weight of body, stroma, oviduct and ovary and higher plasma concentrations of estradiol and lipids at 8 weeks. The best results for weight and length of the intestine and liver weight in this age were also obtained with the white LED, although this type of lamp has provided less weight chest. There was no influence of light sources on bone strength. At 12 weeks there were no differences in the reproductive tract, except the characteristics of folds of magnum and isthmus, which were better with the red LED. Increased bone strength was obtained with the white LED while larger diameter of the eye was observed with red LED or incandescent lamps. No effect of light sources was observed in the chemical composition of carcass and on the circulating levels of AST and ALT, however, the fluorescent lamps increased the levels of γ-GT. In conclusion, all tested light sources are efficient in stimulating the reproductive activity in Japanese quails, however, the photostimulation with white LED has the ability to activate more efficiently the reproductive cycle, anticipating the onset of sexual maturity and favoring the development of reproductive organs after puberty. Furthermore, the photostimulation with this type of lamp has higher efficiency in stimulating the development of organs, in particular the intestines, until the 8th week of life, providing better bone quality during the peak production.